CONTEXTUAL INTERPRETATION OF RELIGIOUS MODERATION VERSES ACCORDING TO ABDURRAHMAN WAHID - Lubis, Nur Hafizoh; Daulay, Sarwedi; Ramadhan, Akbar; Yadi, Nofri (Tanzil: Jurnal Studi Al-Quran, 2024)
Abdurrahman Wahid (Gus Dur) is recognized as the father of Indonesian tolerance because his ideas reflected wasaṭiyyah (moderate) Islamic values. His progressive approach aims to overcome socio-religious and national problems through contextual interpretation of the Qur’an and birth to a moderate thinking model that aligns with principles of tolerance, brotherhood, and nationalism. Research from the Center for the Study of Islam and Society (PPIM) UIN Syarif Hidayatullah Jakarta shows that a lack of external and internal empathy deficits for Muslims as the majority causes low tolerance. Therefore, it is essential to highlight Gus Dur’s thoughts on religious moderation from his work Islamku, Islam Anda, and Islam Kita. Gus Dur views Islam as a unique experience that should be understood, not forced. Gus Dur distinguishes Islam Anda as an obligation to respect the beliefs and traditions held by a particular community. This research was carried out through a literature study using the content analysis method and Gus Dur’s writings, especially my Islam, your Islam, our Islam. The aim is to revitalize the concept of religious moderation in the style of Gus Dur, who prefers to be called the father of humanity. The result shows Gus Dur’s concept of religious moderation, including awareness of religious diversity, implementing the function of religion for the public good, adopting a nationalist orientation, emphasizing interreligious dialogue, and upholding the principles of justice professionalism, and tolerance.